Studies in computer science. Parallel programming paradigm, Per Brinch Hansen : Prentice Hall, Englewood Cliffs, first edition - De Giusti, Armando Eduardo (2000)
In this book, Hansen presents a collection of structured multicomputer programs for computational science, with the unifying idea of programming paradigm.